Respuesta :

Answer:

The solution of the given system is (2,0)

Step-by-step explanation:

Here, the given system of equations is:

x + y = 2    .............. (1)

[tex]y= x^2 - 6x +  8[/tex]  ........  (2)

Now from (1) x = 2 - y

Substitute this value of x = 2- y in (2) ,we get:

[tex]y= (2-y)^2 - 6(2-y) +  8\\\implies y = 4 + y^2 - 4y - 12 + 6y + 8\\or, y^2 + y  = 0\\\implies y(y +1) = 0[/tex]

⇒  y = 0 or,  y = -1

Now, if y = 0, x  = 2

and if x= -1, y = 2-(-1)  = 2+1  = 3, or y = 3

But (x = -1 , y = 3 )is NOT  a solution of (2).

Hence, the solution of the given system is (2,0)

ACCESS MORE